(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
The development of science serves as a guarantee of the development of every state and society. The development of natural and technical sciences creates the basis for achieving great achievements in the economic and production sectors of the country, while the development of social and humanitarian sciences serves to form a strong civil society based on democratic principles in the country.